Sustained Unresponsiveness in Oral Immunotherapy for Cow's Milk Allergy - Kim, Sukyung; Kim, Minji; Kim, Jiwon; Jung, Minyoung; Lee, Ji Young; Ahn, Kangmo; Kim, Jihyun (Journal of Inflammatory and Infectious Medicine, 2025)
Short Communication Sustained Unresponsiveness in Oral Immunotherapy for Cow’s Milk Allergy Sukyung Kim 1,†, Minji Kim 2,†, Jiwon Kim 2, Minyoung Jung 3, Ji Young Lee 4, Kangmo Ahn 1,5 and Jihyun Kim 1,5,* 1 Department of Pediatrics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul 06351, Korea 2 Department of Pediatrics, Chungnam National University Sejong Hospital, Sejong 30099, Korea 3 Department of Pediatrics, Kosin University Gospel Hospital, Kosin University College of Medicine, Busan 49267, Korea 4 Department of Pediatrics, Hallym University Chuncheon Sacred Heart Hospital, Hallym University School of Medicine, Chuncheon 24253, Korea 5 Department of Health Sciences and Technology, Samsung Advanced Institute for Health Sciences & Technology, Seoul 06355, Korea * Correspondence: jhlovechild@gmail.com; Tel.: +82-2-3410-1035; Fax: +82-2-3410-0043 † These authors contributed equally to this work. Received: 8 August 2024; Revised: 16 October 2024; Accepted: 22 November 2024; Published: 13 February 2025 Abstract: Background: We aimed to investigate the efficacy and safety of home-based oral immunotherapy (OIT) in children with cow’s milk (CM) allergy (CMA) and to examine whether sustained unresponsiveness (SU) could be achieved after cessation of OIT. Methods: Children with CMA, aged 3–10 years, were enrolled in the OIT (n = 8) and the control (n = 8) groups. Patients increased the dose of heated milk daily at home during the build-up phase. During the maintenance phase, 100 mL of unheated milk (UM) (3.0 g of CM proteins) was administered daily to the patients for 12 months. Oral food challenge (OFC) tests were performed with a total dose of 200 mL of UM after the build-up phase and four weeks after cessation of CM following the maintenance phase. Results: All patients in the OIT group achieved desensitization after completion of the build-up phase. After 12 months of the maintenance phase and four weeks of the CM restriction period, OFC was performed in six patients in the OIT group. Among them, five (83.3%) patients obtained SU, while none of the patients in the control group achieved tolerance (p = 0.003). During OIT, adverse reactions were reported in seven (87.5%) patients. Anaphylaxis occurred in three (37.5%) patients in the OIT group and in four (50.0%) patients in the control group (p = 1.000). There were no serious adverse or life-threatening events during OIT. Conclusions: Home-based milk OIT is an effective and safe treatment method for SU and desensitization to CMA.